Effects of Learning Style on Achievement of Distance Learners. - Khan, Jamshed; Iqbal, Muhammad Javed (Dialogue (Pakistan))
The study aimed to find out the effect of learning style on achievement of distance learners and was delimited to the learners of Master of Education program at Allama Iqbal Open University Islamabad. The sample was selected through stratified random sampling technique. The learning style of the students was assessed using Grasha-Riechmann Student Learning Styles Scale. The study found that majority of the learners with collaborative learning style followed by participant, Independent, competitive, dependant and avoidant learning styles. It was concluded that learning styles and achievement were not correlated at p< 0.05 except a significant negative correlation between avoidant learning style and achievement score (r =0.159, p<0 .01).